Irrigation and nutrient requirement of garlic (Allium sativum) under south Saurashtra region of Gujarat - SADARIA, S G; MALAVIA, D D; KHANPARA, V D; DUDHATRA, M G; VYAS, M N; MATHUKIA, R K (The Indian Journal of Agricultural Sciences, 2013)
A field experiment ws conducted during winter season (rabi of 1991-92 and 1992-93) on clayey soil of Junagadh to study the effect of irrigation (1.0, 1.2 and 1.4 IW:CPE ratio),nitogen (25,50 and 75 kg N/ha) and phosphorus (11,22 and 33 kg P/ha) on garlic (Allium sativum L.). The crop irrigated at 1.4 irrigation water : commulative pan evaporation (IW:CPE) ratio produced significantly higher bulb yield but remained at par with 1.2 IW:CPE, Maximum net return was secured with irrigation atÂ 1.4 IW:CPE, whereas maximum water-use efficiency at 1.21 IW:CPE. Different levels of N did not exert sighificant influence on bulb yield; however, application of 50 kg N/ha recorded maximum net return and water-use efficiency. Application of 11 kg P/ha recorded significantly equivalent bulb yield to that of 33 kg P/ha and realized maximum net return.